A avaliação no processo ensino/aprendizagem: os desafios postos pelas múltiplas faces do cotidiano - Maria Teresa Esteban (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
The article presents a reflection on the daily routine of an ordinary school, giving special attention to evaluation, a practice which is traditionally immersed in predictability, repetition and knowledge, but which also contains within itself the opposing possibilities. It raises for discussion the daily process of evaluation of a class with supposed learning difficulties, in which it was difficult to classify the children in accordance with previously established standards, the attribution of marks, and even how to distinguish right from wrong. For the teachers one question was central: how to teach in a school which accepts heterogeneity as one of the pillars of pedagogical practice? The search for a reply mobilised the school in the sense of redefining its practice with emphasis on evaluation. Motivated by an end to their certainties the teachers constructed ways of facing up to the challenge.